STARATEGI PEMBELAJARAN DALAM MENCAPAI TUJUAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Maemunah Maemunah (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2020)
Learning strategy is a set of methods designed by a teacher that must be adapted to the conditions and conditions that exist in his school. The more appropriate the strategy chosen by a teacher in teaching and learning activities in schools, the greater the chance of achieving the expected learning goals. Educational experts who prioritize the importance of learning strategies that must be considered by a teacher in the learning process. Like Mulyasa's opinion, pleasant learning is a learning process in which there is a strong cohesion between the teacher and students, without feeling forced or depressed. Fun learning is a pattern of good relations between teachers and students in the learning process. Some strategies that can be used by a teacher in the learning process contained here are Direct Learning Strategies, Indirect Learning Strategies, Interactive Learning Strategies, Learning Strategies through Experience, Independent Learning Strategies, Jigsaw Cooperative Strategies, Problem Based Learning Strategies, Contextual Learning Strategies, and Expository Learning Strategies (SPE).